The celebrity endorser effects : an examination of source characteristics on brand image building for consumer goods products - Phang, Ing (2001)
When a consumer chooses a certain brand, many factors actually influence his or her purchase decision. Marketers would like very much to attribute this to the influence of promotion, but other Ps for instance distribution (place), product itself and price are also play their part in influencing a person purchase decision making. Marketers now realize the importance of people influence in the success of their business. The found out endorsers could have a greater ability to change consumers' brand preferences than other advertisements. Endorsers can also catch their target markets' attention and stimulate purchase. As such the purpose of the study is to determine if there is any significant relationship between celebrity endorser's characteristics and brand image building of the consumer products. In addition, the study considers if personal influences like social-demographic factors have any bearing on the relationship mentioned. For the study, 300 respondents from the three public universities in Klang Valley were surveyed using self-administrated questionnaire. Respondents are divided into two categories: undergraduates and postgraduates students. This study was conducted by using non-probability-sampling method. The hypotheses are tested using regression models and the correlation among the variables is examined. The reliability and validity of the factors are also examined to ensure the results of the study. The study result showed that the celebrity characteristics such as credibility, attractiveness and meaningfulness had significant influence on the consumer product's brand image in consumers' perception.